The efficacy and acceptability of psychological interventions for adult PTSD: A network and pairwise meta-analysis of randomized controlled trials - Hoppen, Thole H; Jehn, Marvin; Holling, Heinz; Mutz, Julian; Kip, Ahlke; Morina, Nexhmedin (Journal of consulting and clinical psychology, 2023)
A comprehensive quantitative summary of the efficacy and acceptability of psychological interventions (PIs) for adult posttraumatic stress disorder (PTSD) is lacking. We conducted a systematic literature search to identify randomized controlled trials (RCTs) examining the efficacy and acceptability (all-cause dropout) of psychological interventions (i.e., trauma-focused cognitive behavior therapy [TF-CBT], eye movement desensitization and reprocessing [EMDR], other trauma-focused interventions and non-trauma-focused interventions). One hundred fifty-seven RCTs were included comprising 11,565 patients. Most research (64% of RCTs) accumulated for TF-CBT. In network meta-analyses, all therapies were effective when compared to control conditions. Interventions did not differ significantly in their efficacy. Yet, TF-CBT yielded higher short- ( = 0.17, 95% CI [0.03-0.31], number of comparisons kes = 190), mid- (i.e., ≤5 months posttreatment, = 0.23, 95% CI [0.06-0.40], kes = 73) and long-term efficacy (i.e., >5 months posttreatment, = 0.20, 95% CI [0.04-0.35], kes = 41) than non-trauma-focused interventions. There was some evidence of network inconsistencies, and heterogeneity in outcomes was large. In pairwise meta-analysis, slightly more patients dropped out from TF-CBT than non-trauma-focused interventions (RR = 1.36; 95% CI [1.08-1.70], kes = 22). Other than that, interventions did not differ in their acceptability. Interventions with and without trauma focus are effective and acceptable in the treatment of PTSD. While TF-CBT yields the highest efficacy, slightly more patients discontinued TF-CBT than non-trauma-focused interventions. Altogether, the present results align with results of most previous quantitative reviews. Yet, results need to be interpreted with caution in light of some network inconsistencies and high heterogeneity in outcomes. (PsycInfo Database Record (c) 2023 APA, all rights reserved).